Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20546/ijcmas.2018.708.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sources and Levels of Sulphur on Growth and Yield of Maize (Zea mays L.)

Abstract: to compute the optimum dose and source of sulphur in maize and to evaluate the impact of sulphur on growth, yield attributes and yield of maize. The experiment was carried out with three different sources of sulphur (Gypsum, Ammonium Sulphate and Bentonite Sulphur) and three levels (S @ 40 kg ha -1 , S @ 60 kg ha -1 and S @80 kg ha -1 ) and one source as urea, DAP and MOP and another source as urea, SSP and MOP comprising of eleven treatment combinations which were laid out in randomized block design and repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Irfan et al, (2015) [16] documented higher values for sulphur concentration (0.44%) with 75 kg ha -1 than control (0.09%) in maize. Padma et al, (2018) [31] concluded that nutrient uptake of plants and grain were higher with application of 60 and 80 kg ha -1 of sulphur in maize crop from his study. Das et al, (1975) [9,34] documented that application of sulphur at 30 kg ha -1 gave 8 % increase in methionine and 5% increase in cystiene and protein content with 1% in maize crop.…”
Section: Effect Of Sulphur Application On Nutrient Uptake Of Maizementioning
confidence: 95%
See 3 more Smart Citations
“…Irfan et al, (2015) [16] documented higher values for sulphur concentration (0.44%) with 75 kg ha -1 than control (0.09%) in maize. Padma et al, (2018) [31] concluded that nutrient uptake of plants and grain were higher with application of 60 and 80 kg ha -1 of sulphur in maize crop from his study. Das et al, (1975) [9,34] documented that application of sulphur at 30 kg ha -1 gave 8 % increase in methionine and 5% increase in cystiene and protein content with 1% in maize crop.…”
Section: Effect Of Sulphur Application On Nutrient Uptake Of Maizementioning
confidence: 95%
“…Kumar et al, (2015) [47,52] registered maximum gross income, net returns, benefit cost ratio were higher with application of sulphur at 50 kg ha -1 and remained at par with 25 kg ha -1 in maize crop. Padma et al, (2018) [31] registered a maximum gross returns and benefit cost ratio with application 60 kg ha -1 of sulphur than control in maize.…”
Section: Effect Of Sulphur Application On Nutrient Uptake Of Maizementioning
confidence: 99%
See 2 more Smart Citations
“…Actual crop water use is directly related to ET. Maize is an efficient user of water in terms of total dry matter production, and among cereals, it is potentially the highest‐yielding grain crop (Padma et al, 2018). The values of K c reported by various researchers around the globe have been compiled and are presented in Table 3.…”
Section: Estimation Of the Crop Coefficientmentioning
confidence: 99%